Dual extraction of essential oil and podophyllotoxin from creeping juniper (Juniperus horizontalis). - Charles L Cantrell (Public Library of Science (PLoS), 2014)
Juniperus horizontalis Moench (Family Cupressaceae), commonly called creeping juniper, is a widely distributed species in the United States and much of Canada. It is potentially a source for two important chemical products, the anticancer drug synthetic precursor, podophyllotoxin and essential oils. The objectives of this study were to ascertain the likelihood of utilizing J. horizontalis needles for the simultaneous production of both (-)-podophyllotoxin and essential oil components and to determine the optimum distillation time (DT) needed for the production of essential oil containing a specific ratio of constituents. Eleven different distillation times were tested in this study: 20, 40, 80, 160, 180, 240, 480, 600, 720, 840, and 960 min. Total essential oil content increased with increasing distillation time from a minimum of 0.023% at 20 min to a maximum of 1.098% at 960 min. The major constituents present in the oil were alpha-pinene, sabinene, and limonene. The percent concentration of sabinene in the essential oil varied from a high of 46.6% at 80 min to a low of 30.2% at 960 min, that of limonene changed very little as a result of distillation time and remained near 30% for all distillation times, whereas the concentration of alpha-pinene was 9.6% at 20 min DT and decreased to 4.2% at 960 min. Post distillation analysis of needles revealed elevated amounts of (-)-podophyllotoxin remaining in the tissue varied in the amount of podophyllotoxin present, from a low of 0.281% to a high of 0.364% as compared to undistilled needles which gave 0.217% podophyllotoxin. As a result of this study, specific essential oil components can now be targeted in J. horizontalis by varying the distillation time. Furthermore, needles can be successfully utilized as a source of both essential oil and podophyllotoxin, consecutively.